English Language Learning through Games - Muqdad Al-karawi (Educational Challenges)
Nowadays there are controversial views regarding the acquisition, learning of languages by children. It is commonly agreed that language is learned through imitation, especially as per behavioral theories. This implies that both first and second or foreign languages are learned in the same way. They say, learning languages irrespective of whether they are first, second, third, or nth follows the same steps. The purpose of the study is to point the main ideas of English language learning using games. The objectives are to study the problem of teaching-learning English as a foreign language, to study trends in teaching a second or foreign language, to study related to language games and different language games used in the classroom for teaching English as a foreign language; it was also examined the impact of language games on classroom interaction. The methodology includes a literature review related to the topic; methods of analysis, classification, and comparative analysis. The most important results are understanding how children learn a language, basics of EFL teaching-learning, comparing monitor and input hypothesis, some theories such as accommodation theory, multiple intelligence, different types of interaction through language games. It is concluded that it is necessary to make EFL learning enjoyable, playful and stress-free. The best way to do this is to introduce the new language through games. When using games for educational purposes in a classroom setting is accepted as fruitful and beneficial, you can begin to devise language games of different types. Games for teaching EFL have a number of advantages in addition to the teaching language elements.